2017
DOI: 10.1016/j.sleh.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in short and long sleep durations between blacks and whites attributed to emotional distress: analysis of the National Health Interview Survey in the United States

Abstract: Individuals of the black race/ethnicity or those reporting greater levels of emotional distress are more likely to report short or long sleep duration. Emotional distress might partially explain racial/ethnic differences in unhealthy sleep duration between blacks and whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Among whites, increasing professional responsibility within a given industry was associated with longer self-reported sleep duration whereas among blacks, increasing professional responsibility was associated with self-reported shorter sleep [15]. Reports of depression and anxiety were related to self-reported shorter sleep among blacks but not among whites [16]. Thus, from this analytic approach one cannot determine whether the covariates actually account for racial/ethnic differences but can indicate the relative importance of the covariate for one group or the other.…”
Section: Introductionmentioning
confidence: 89%
“…Among whites, increasing professional responsibility within a given industry was associated with longer self-reported sleep duration whereas among blacks, increasing professional responsibility was associated with self-reported shorter sleep [15]. Reports of depression and anxiety were related to self-reported shorter sleep among blacks but not among whites [16]. Thus, from this analytic approach one cannot determine whether the covariates actually account for racial/ethnic differences but can indicate the relative importance of the covariate for one group or the other.…”
Section: Introductionmentioning
confidence: 89%
“…Of the few prior nationally representative studies of the US, only sleep duration was assessed, which is not comprehensive. [18][19][20][21] Despite this fact, these studies have shown that the association between insufficient sleep and SPD tend to be stronger among racial/ethnic minority groups.…”
Section: Introductionmentioning
confidence: 98%
“…All models were adjusted for the following potential confounders: age, sex/gender, educational attainment, annual household income, occupational class, employment status, alcohol consumption, and "ideal" cardiovascular health. [19][20][21]33 A two-sided p-value of 0.05 was used to determine statistical significance.…”
mentioning
confidence: 99%
“…Indeed, there is some evidence that black and white adults may interpret questions about sleep duration differently. 33,34 Another possibility is short sleep duration may be a marker for another confounding variable such as employment status. Full-time employed individuals tend to report short sleep durations.…”
Section: Discussionmentioning
confidence: 99%